Arnold Transform-Lifting Wavelet Transform and Singular Value Decomposition Based Alpha Blending Image Steganography for Secure Communication - Tevaramani , Saleem S.; J. , Ravi (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Image steganography is an artistic approach used to conceal secret data within a cover image (CI) while maintaining its visual quality. This paper presents a strategy for image steganography by applying Arnold Transformation (AT) to Secret Image (SI), Singular Value Decomposition (SVD), and Lift Wavelet Transformation (LWT) to CI and SI. AT is enforced on the RGB plane of SI, and the LWT is engaged to decompose the image into approximations and detail coefficients, allowing for the identification of areas suitable for embedding without noticeable changes. The SVD is operating on the approximation coefficients, resulting in the U, singular value S, and V matrices. By modifying the singular values, secret data is embedded. The proposed method offers improved robustness and security as modifications are distributed across various frequency components, making it challenging for unauthorized parties to detect the confidential information. Experimental results demonstrate that the combination of LWT and SVD yields effective results, i.e., Mean Squared Error (MSE) and Peak Signal to Noise Ratio (PSNR) with minimal visual distortion. However, the embedded information may still be susceptible to specific steganalysis attacks, necessitating additional security measures for sensitive data.